Multiple Perspective-Taking, Diversity, and External Network in Strategy Development - Yoko TAKEDA (AAOS Transactions)
This study investigates the creative processes in corporate strategy development by comparing them to those in business planning, hardware, and software development projects （Takeda, 2023）. A model of improving creative performance including team diversity, network diversity, and multiple perspective-taking was examined with corporate-level strategy development teams （n=472）. Results indicated that both functional and age diversity indices had an indirect effect on strategic creativity, mediated through network diversity and multiple perspective-taking, a mechanism consistent with project-level findings. In contrast, gender diversity did not show the creative mechanism through network diversity and/or perspective-taking; national diversity did not demonstrate such a mechanism through network diversity. Moreover, direct effects of diversity on strategic creativity were also significant; such effects were not observed at the project level.